Association of thyroid disorders with diabetes: A cross-sectional study - MUBASHIR ZAFAR; SYED MONWAR ALAM SHAHID; REEM FALAH ALSHAMMARI; MOHD ADNAN KAUSAR; TARIG A. N. GINAWI; ABDUL WAHAB HATIM; ABDUL MAJEED WADI; HAMAD ALI; ABDUL AZIZ HAMED; MOATH SALEH AL-ZAHRANI; ALI HUSSAIN; ABDULAZIZ SAUD ALDUHAIM; ABDULMAJEED MOHAMMED (Nusantara Bioscience, 2022)
Abstract. Zafar M, Shahid SMA, Alshammari RF, Kausar MA, Ginawi TAN, Hatim AW, Wadi AM, Ali H, Hamed AA, Al-Zahrani MS, Hussain A, Alduhaim AS, Mohammed A. 2022. Association of thyroid disorders with diabetes: A cross-sectional study. Nusantara Bioscience 14: 135-140. Two common endocrine disorders that correlate with each other are diabetes mellitus (DM) and thyroid dysfunction (TD). Undiagnosed thyroid disorders (TD) have a high risk for diabetes mellitus (DM) patients. A common complication among these patients is cardiovascular disease. This study aims to assess the association of TD among diabetes patients. It is a cross-sectional study, and 338 patients with type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) were observed through a simple random sampling method from a public sector hospital. The diabetes status of patients was confirmed through clinical and laboratory investigation. Those patients who were under treatment of thyroid were excluded from the study. The chi-square test was used for analysis, and a p-value <0.05 was considered significant. The frequency of TD among diabetic patients was 47.6%. The main type of TD was subclinical hypothyroidism, and its prevalence is 43.8% and 23.5% among patients with T1DM and T2DM, respectively. Subclinical hyperthyroidism prevalences are 12.3% and 24.4% among TIDM and T2DM patients, respectively. The study found a high-frequency rate of TD among DM patients. Therefore, there is a need for regular screening of DM patients for TD and increased awareness regarding TD among DM patients.